Physiological and Behavioral Changes in Honey Bees (Apis mellifera) Induced by Nosema ceranae Infection - Goblirsch, Mike (Public Library of Science, 2013)
Persistent exposure to mite pests, poor nutrition, pesticides, and pathogens threaten honey bee survival. In healthy colonies, the interaction of the yolk precursor protein, vitellogenin (Vg), and endocrine factor, juvenile hormone (JH), functions as a pacemaker driving the sequence of behaviors that workers perform throughout their lives. Young bees perform nursing duties within the hive and have high Vg and low JH; as older bees transition to foraging, this trend reverses. Pathogens and parasites can alter this regulatory network. For example, infection with the microsporidian, Nosema apis, has been shown to advance behavioral maturation in workers. We investigated the effects of infection with a recent honey bee pathogen on physiological factors underlying the division of labor in workers. Bees infected with N. ceranae were nearly twice as likely to engage in precocious foraging and lived 9 days less, on average, compared to controls. We also show that Vg transcript was low, while JH titer spiked, in infected nurse-aged bees in cages. This pattern of expression is atypical and the reverse of what would be expected for healthy, non-infected bees. Disruption of the basic underpinnings of temporal polyethism due to infection may be a contributing factor to recent high colony mortality, as workers may lose flexibility in their response to colony demands.